Modeling Biomass Conversion in Raceway Zone of Blast Furnace Using Resolved Lagrangian Particle Model - Matthias Kiss; Christine Gruber; Michael Harasek; Markus Bösenhofer (Energies)
This study numerically investigates the suitability of biomass particles of varying diameters as alternative reducing agents in the blast furnace raceway zone, where harsh conditions can create internal gradients affecting conversion. An internally resolved 1D Lagrangian particle model, fully integrated into the open-source CFD toolbox OpenFOAM®, is used to model temperature and species gradients within thermally thick particles. The particle model is coupled with the surrounding Eulerian phase and includes drying, pyrolysis, oxidation, and gasification submodels. Results show that only biomass particles smaller than 250 μm fully convert in the raceway, while larger particles carry unconverted material beyond, potentially reducing blast furnace efficiency.